Manipulation of decellularized porcine scaffolds for tissue engineering vascular grafts - Sheridan, William (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
The prevalence of vascular disease continues to increase worldwide, the treatment for which relies heavily on diseased vessel replacement. Tissue engineering vascular grafts potentially offers a new solution for addressing the shortage of autologous vessel grafts. Challenges such as suitable mechanical properties, viable cell sources, inefficient seeding techniques, lengthy manufacturing times, sustainable shelf life and high costs have hindered this translation. Decellularized scaffolds could potentially offer a solution to this clinical problem; however, their translation has been limited by their highly dense matrix architecture which can prevent cell repopulation.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin